2016
DOI: 10.1136/tobaccocontrol-2016-053022
|View full text |Cite
|
Sign up to set email alerts
|

Costs, revenues and profits: an economic analysis of smallholder tobacco farmer livelihoods in Malawi

Abstract: Background The preservation of the economic livelihood of tobacco farmers is a common argument used to oppose tobacco control measures. However, little empirical evidence exists about these livelihoods. We seek to evaluate the economic livelihoods of individual tobacco farmers in Malawi, including how much money they earn from selling tobacco, and the costs they incur to produce the crop, including labour inputs. We also evaluate farmers’ decisions to contract directly with firms that buy their crops. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 22 publications
5
60
0
Order By: Relevance
“…First, we found that input supports, such as subsidies on fertilizers, seeds or farm equipment, generally resulted in positive changes in production and farm income. This finding corresponds with research in the tobacco control literature that finds that inputs are a key factor in farmers' decision to enter into contract with leaf buying companies [22,23]. Second, these findings also point consistently to the high level of importance of education and support for farmers, most often in the form of extension services.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…First, we found that input supports, such as subsidies on fertilizers, seeds or farm equipment, generally resulted in positive changes in production and farm income. This finding corresponds with research in the tobacco control literature that finds that inputs are a key factor in farmers' decision to enter into contract with leaf buying companies [22,23]. Second, these findings also point consistently to the high level of importance of education and support for farmers, most often in the form of extension services.…”
Section: Discussionsupporting
confidence: 84%
“…For example, Natarajan points out that tobacco farmers in South India grow the crop due to its amenability to the environment and the lack of profitable alternatives [87]. Similarly, studies in Malawi and Kenya also find that farmers continue to grow tobacco, despite limited income, due to a perceived lack of alternatives [22,23]. This review provides important direction for research on alternatives.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, rigorous empirical findings across multiple and varied contexts has helped to generate evidence that small-scale tobacco farmers are rarely economically prosperous and that tobacco control has very little short-term effect on them, in countries such as Kenya, (Magati, Li, Drope, Lencucha, & Labonté, 2016). Malawi, (Makoka, Drope, Appau, et al, 2016) and Zambia. (Goma, Drope, Zulu, Li, & Banda, 2017).…”
Section: Informing Advocacy Effortsmentioning
confidence: 99%
“…In a study of such tenants in Malawi in 2000, more than one quarter had no education, 40% reported they could not read, 40% reported they could not write and over 40% said they could not work with numbers 25 . Since 2005, contract farming – in which farmers sell directly to leaf buyers who also offer credit and technical support – has become more common in Malawi 27 . As farmers who enter into contracts with industry tend to become indebted quickly, it is worrying that, by 2010, an estimated 10% of the burley tobacco farmers in Malawi had become contract farmers 17 , 26 …”
Section: Tobacco Cultivationmentioning
confidence: 99%